2017
DOI: 10.1007/s00424-017-1964-4
|View full text |Cite|
|
Sign up to set email alerts
|

Neurobiology of local and intercellular BDNF signaling

Abstract: Brain-derived neurotrophic factor (BDNF) is a member of the neurotrophin family of secreted proteins. Signaling cascades induced by BDNF and its receptor, the receptor tyrosine kinase TrkB, link neuronal growth and differentiation with synaptic plasticity. For this reason, interference with BDNF signaling has emerged as a promising strategy for potential treatments in psychiatric and neurological disorders. In many brain circuits, synaptically released BDNF is essential for structural and functional long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
207
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(228 citation statements)
references
References 174 publications
(368 reference statements)
5
207
0
16
Order By: Relevance
“…The inactive form of CREB seems to bind BDNF promoter, after which CREB phosphorylation recruits transcription factor components to the promoter and initiates gene transcription of BDNF. p‐CREB is therefore a vital upstream factor of BDNF expression (Sasi, Vignoli, Canossa, & Blum, ). We measured the levels of BDNF expression and CREB phosphorylation to elucidate the possible molecular mechanism and found that early postnatal exposure of PM2.5 reduced BDNF expression levels in the hippocampus in immature and mature rats.…”
Section: Discussionmentioning
confidence: 99%
“…The inactive form of CREB seems to bind BDNF promoter, after which CREB phosphorylation recruits transcription factor components to the promoter and initiates gene transcription of BDNF. p‐CREB is therefore a vital upstream factor of BDNF expression (Sasi, Vignoli, Canossa, & Blum, ). We measured the levels of BDNF expression and CREB phosphorylation to elucidate the possible molecular mechanism and found that early postnatal exposure of PM2.5 reduced BDNF expression levels in the hippocampus in immature and mature rats.…”
Section: Discussionmentioning
confidence: 99%
“…Sigma receptors have emerged as targets for novel therapeutic applications in neurodegenerative diseases 59,60 , since their activation is linked with neuroprotection 61 . Sigma-1 receptor activation results in expression of BDNF, which mediates phosphorylation of the tyrosine kinase B (TrkB) 62 , which initiates a signaling cascade that involving MEK and ERK that causes activation of MAPK 63,64 . We demonstrated that PS treatment of cells activated a BDNF-mediated activation of MAPK signaling pathway by examining the effect of PS treatment on several genes known to be induced by BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…The BDNF/TrkB receptor complex plays critical roles in developmental processes, regulation of neuro-, glio-, and synaptogenesis, neuroprotection, and controlling of short-and long-lasting synaptic interactions that influence mechanisms of memory and cognition (Foltran and Diaz 2016, Sasi et al 2017, Messaoudi et al 2002, Gruart et al 2006, Whitlock et al 2006. Mariga et al (2015) reported that reduction of BDNF in the cultured rat hippocampal neurons was related to decreased expression of the genes that are functionally linked to vesicular trafficking and synaptic communication.…”
Section: Discussionmentioning
confidence: 99%